2011
DOI: 10.1002/jmri.22758
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of functional MRI localization within the human somatosensory cortex

Abstract: Purpose: To evaluate the effect of fMRI localization approaches and region size on the reproducibility of digit localization in the human somatosensory cortex. Materials and Methods:Vibrotactile stimulation was applied to digits 2 and 4 producing cortical activation sites relating to each digit. Thirteen subjects were scanned twice on separate occasions in a 3 Tesla scanner using a voxel size of 2 mm. Regions of activity were thresholded to different sizes varying from 50 to 1000 voxels. Three measures of posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The digit localisation paradigm provided robust digit localisation in 24 out of the 29 participants for combined pre and post co-activation data. An area of 200 contiguous voxels was identified for D2 and D4 for each individual, based on previous work showing this size region to be highly reproducible (Vidyasagar and Parkes, 2011). Participants were excluded from subsequent analysis (3 participants from the synchronous and 2 participants from the asynchronous conditions, leaving 13 in the synchronous condition, including 10 returners, and 11 in the asynchronous condition) as they had failed to show 200 contiguously activated voxels at p < 0.01 uncorrected for both digits.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The digit localisation paradigm provided robust digit localisation in 24 out of the 29 participants for combined pre and post co-activation data. An area of 200 contiguous voxels was identified for D2 and D4 for each individual, based on previous work showing this size region to be highly reproducible (Vidyasagar and Parkes, 2011). Participants were excluded from subsequent analysis (3 participants from the synchronous and 2 participants from the asynchronous conditions, leaving 13 in the synchronous condition, including 10 returners, and 11 in the asynchronous condition) as they had failed to show 200 contiguously activated voxels at p < 0.01 uncorrected for both digits.…”
Section: Resultsmentioning
confidence: 99%
“…For each pre, post and return session, digit regions were defined following the approach described in a previous study (Vidyasagar and Parkes, 2011), which showed a high level of reproducibility across sessions. In brief, the t-statistic contrast maps were first thresholded to a significance level of p < 0.01, uncorrected, for visual inspection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, most human S1 functional imaging studies have focused on the topographic organization of S1 cortex or its subdivisions [Nelson and Chen, 2008;Sanchez-Panchuelo et al, 2010;Schweisfurth et al, 2011;Schweizer et al, 2008;Vidyasagar and Parkes, 2011]. Few studies have examined the fine-scale functional organization of area 3b and area 1 in humans, partially due to the constraints of signal-or contrast-to-noise ratio of conventional imaging methods [Martuzzi et al, 2012;Sanchez-Panchuelo et al, 2012].…”
Section: Introductionmentioning
confidence: 99%